HLA in Southern Thai-Muslims - Pimol Chiewsilp (2018)
One hundred and two Southern Thai-Muslims (STM) from Nakhon Si Thammarat province were studied for HLA class I and II by SSP ARMS-PCR and PCR-SSO, respectively. The allele frequencies, haplotype frequencies, delta value and linkage disequilibrium between alleles were expressed. The most frequent alleles for HLA-A, HLA-B and HLA-C were A*24(02,03), A*11 (01,02), A*02(01,03,05-07,11): B*15(01,04-07,12,19,20), B*07(02-05), B*51(01-05)/B*52 (011,012); and Cw*07(01-03), Cw*04(01,02), Cw*08(01-03), respectively. The HLA class II alleles frequently found were DRB1*1202, DRB1*15021, DRB1*0701; DRB3*0301; DRB5* 0101; DQA1*0101, DQA1*0103, DQA1*0601; DQB1*0301, DQB1*0501, DQB1*0201; and DPB1*1301, DPB1*2301 and DPB1*0501. Two common HLA class I and II haplotypes with significant linkage disequilibrium were A*24 (02,03)-Cw*08 (01-03)-B*15 (01,04-07,12,19,20) -DRB1*1202 and A*33 (01,02)-Cw*0302-B*5801-DQB1*0201. The absence of B*27 and DRB1 *1401, the presence of A*2301 and high frequency of A*68 were observed in STM. Conclusion : Certain level of genetically distinction among STM, CT and NET existed. However, the genetic diversity of STM was relatively closer to CT than NET.